Confronting the Past Abuses: Indonesia and Southeast Asia - Priyambudi Sulistiyanto (Jurnal Theologia, 2021)
This article examines the politics of reconciliation in Indonesia and Southeast Asia. It focuses in particular on the case of Talangsari killings in Indonesia and makes a regional comparison with Thailand, Cambodia, the Philippines and Myanmar. The Indonesian experience illustrates some of the complex issues that arise when attempts are made to dealing with past abuses, especially in the context of the constraints and possibilities faced by new democracies. In a comparative perspective what is being experienced in Indonesia is not new in the sense that, as argued by scholars elsewhere, new democracies also have to face this kind of situation.1 This article argues that dealing with the past human rights abuses brings about real power struggles among the contending actors and power holders and it reflects the power structures within and outside the country. It is suggested that there is no “universal” model for dealing with past human rights abuses but some form of accountability which brings together the elements of prosecution, reconciliation and forgiveness could be considered.